The Power of Knowing a Woman Is in Charge: Lessons from a Randomized Experiment - Dobrescu, Loretti; Motta, Alberto; Shanker, Akshay (Management Science, 2024)
As part of a term-long anonymous assessment, thousands of undergraduate university students were divided into groups, each led by a randomly selected peer. The leader’s gender had no effect on the assessment’s outcomes, but female students led by a female peer achieved 0.26 standard deviations (SD) higher course grades when the gender of the leader was revealed. They also outperformed by 0.22 SD their counterparts in groups in which the leader’s gender was revealed to be male. The mechanism involved attempting more difficult practice questions. Our structural estimates suggest this operated via a stereotype threat reversal that reduced anxiety. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.00325 .